The Criticism of Land Procurement Law to Improve Landowners Welfare in Indonesia - Henny Saida Flora; Grenaldo Ginting; Ningrum Ambarsari; Marjan Miharja; Dolfries Jakop Neununy (Jurnal Smart Hukum (JSH), 2024)
The Indonesian Land Acquisition Law serves as a crucial legal instrument in facilitating national development. However, the implementation of this law often gives rise to criticism, particularly with regard to the welfare of landowners whose property is acquired for the public good. This article seeks to provide a critical analysis of the implementation of the Land Acquisition Law in Indonesia and its impact on the welfare of landowners. The methodology employed is a literature review that examines previous research, related legislation, and cases of land acquisition implementation. The findings indicate that, despite the law's objective of enhancing welfare through fair compensation, there are still shortcomings in its implementation that result in injustice to landowners.